Extraction of carboxin and bensulfuron-methyl using cysteine-functionalized chitosan-coated magnetic nanoparticles and response surface methodology. Issue 14 (22nd September 2021) - Kouhestani, Hossein; Ebrahimi, Pouneh
ABSTRACT: In the proposed method cysteine-functionalized chitosan-coated magnetic nanoparticles were synthesized and used as an effective adsorbent for the extraction of carboxin and bensulfuron-methyl. The experiments were performed according to an orthogonal rotatable Box-Behnken design. The results showed that the limits of detection, quantification values, and linear ranges were 0.6, 2.0 µg.L −1, and 2–1000 µgL −1 for carboxin, and 0.3, 1.0 µgL −1, and 1–1000 µgL −1 for bensulfuron-methyl. The proposed method was applied to spiked real samples. The percentage of recovery values (91.53%-98.46%) with low relative standard deviation (≤4.6%) demonstrated excellent repeatability and applicability of this adsorbent to water samples. Abbreviations: Aminopropyl triethoxysilane, APTES; Box-Behnken design, BBD; Central composite design, CCD; Chitosan, CS; Double-distilled deionized water, DDW; Extraction recovery, ER; Fourier transform infrared, FT-IR; Liquid-Liquid extraction, LLE; Liquid-Solid extraction, LSE; Maximum residue limits, MRL; Magnetic dispersive-solid-phase extraction, MD-SPE; Magnetic nanoparticles, MNPs; Multiple linear regression, MLR; Response surface methodology, RSM; Solid-phase extraction, SPE; Thermal gravimetric analyses, TGA; Tetraethyl orthosilicate, TEOS; X-ray diffraction, XRD.